Analysis and optimization of a mode of industrial product processing at an electron accelerator - Nikiforov, V.I.; Pomatsalyuk, R.I.; Rogov, Yu.V.; Tenishev, A.Eh.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2015)
By means of computer simulation, the factors determinating non-uniformity of the volume distribution of the absorbed dose at product processing by scanned electron beam, namely, the energy spectrum and scanning mode, product density and homogeneity of its distribution, as well as the distance between the objects moving through the irradiation zone, are studied. On the basis of the PENELOPE-2008 package, a code for calculating the dose distribution and its non-uniformity coefficient with due regard to the beam characteristics, surface density and velocity of the object, has been developed. Verification of the code was carried out by comparison of simulation results with the experimental data obtained using a reference polystyrene calorimeter RISO as well as by dose mapping in a standard phantom.